Determination of Optimal Sample Plot Dimension for Measuring Species Diversity of Plants in Beach Forest Ecosystem - Siddiq Nurkholis; Yanto Santosa; Iwan Hilwan (Jurnal Ilmu Kehutanan, 2023)
Biodiversity measurement served as baseline data for the development of effective conservation plans. The accuracy of the measurement was highly dependent on the size of the sample plot. Even though Indonesia had various ecosystems, the standard sample plot size for measuring plant species diversity was only available for lowland, lower montane, and mangrove forests. Therefore, this study aimed to determine the optimal dimension of plots for measuring plant species diversity in coastal forest ecosystems. The data was collected in Ujung Kulon National Park using various dimensions of sample plots ranging from 2 m × 2 m to 150 m × 50 m. Furthermore, the rarefaction method and species-area curve were used to examine the data. The curves showed that the optimal sample plot dimensions for seedling, sampling, and pole levels were 110 m × 50 m and 150 m × 50 m for tree stages.